Interdisciplinary Approaches to Disability : Looking Towards the Future: Volume 2 - Ellis, Katie; Garland-Thomson, Rosemarie; Kent, Mike; Robertson, Rachel; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
How can a deep engagement with disability studies change our understanding of sociology, literary studies, gender studies, aesthetics, bioethics, social work, law, education, or history? Interdisciplinary Approaches to Disability (the companion volume to Manifestos for the Future of Critical Disability Studies) identifies both the practical and theoretical implications of such an interdisciplinary dialogue and challenges people in disability studies as well as other disciplinary fields to critically reflect on their professional praxis in terms of theory, practice, and methods.Topics covered include interdisciplinary outlooks ranging from media studies, games studies, education, performance, history and curation through to theology and immunology. Perspectives are drawn from different regions from the European Union to the Global South with chapters that draw on a range of different national backgrounds. Our contributors who write as either disabled people or allies do not proceed from a singular approach to disability, often reflecting different or even opposing positions. The collection features contributions from both established and new voices in international disability studies outlining their own visions for the future of the field. Interdisciplinary Approaches to Disability will be of interest to all scholars and students working within the fields of disability studies, cultural studies, sociology, law history and education. The concerns raised here are further in Manifestos for the Future of Critical Disability Studies.
List of contributors; Acknowledgements; Chapter 1: Looking to the Future for Critical Disability Studies: Disciplines, Perspectives and Manifestos (Mike Kent, Katie Ellis, Rachel Robertson and Rosemarie Garland Thomson); Part One, Disciplines of Media and Communication; Chapter 2: Teaching disability studies and building a community of pedagogy through Facebook (Beth A. Haller and Matthew Wangeman); Chapter 3: Disability, Higher Education and E-learning: Moving beyond accessible web design (Mike Kent, Katie Ellis, Tim Pitman, Leanne McRae and Nathalie Latter); Chapter 4: On dis/ability within game studies: The discursive construction of ludic bodies (Simon Ledder); Chapter 5: Disability studies, big data and algorithmic culture (Olivia Banner); Part Two, Disciplines of Culture and Arts; Chapter 6: Sharing and shaping space: Notes toward an aesthetic ecology (Gretchen E. Henderson); Chapter 7: Why critical disability studies needs a cultural model of dis/ability (Anne Waldschmidt); Chapter 8: Celebrating the able body in contemporary disAbility performance (Suzanne Ingelbrecht); Chapter 9: Re-thinking care: Disability and narratives of care in Dinah Mulock Craiks A noble life (1866) (Theresa Miller); Chapter 10: The politics of creative access: Guidelines for a critical dis/ability curatorial practice (Amanda Cachia); Chapter 11: Towards a critical disability studies model of teacher education (Saili S. Kulkarni); Part Three, Disciplines of Complexity and Innovation; Chapter 12: Complexity and disability: drawing from a complexity approach to think through disability at the intersections (Louisa Smith and Leanne Dowse); Chapter 13: Towards a crip methodology for critical disability studies (Louise Hickman and David Serlin); Chapter 14: Inserting disability pedagogies in mutable configurations of space and interaction (Brian Goldfarb and Suzanne Stolz); Chapter 15: Mobilising historical knowledge: Locating the disability archive (Natalie Spagnuolo); Chapter 16: Cripping immunity: Disability and the immune self (Travis Chi Wing Lau); Chapter 17: Theologising disability: Intersections of critique and collaboration (Sarah Jean Barton); Part Four, Perspectives of Place; Chapter 18: Hello from the other side: Why Iran remains excluded from global disability studies (Negin Hosseini Goodrich); Chapter 19: Misrecognising persons with disabilities in the Global South: The need for a comparative disability studies framework (Stephen Meyers); Chapter 20: An investigation into the social integration of people with disabilities in the European Union using a novel approach to cultural consonance analysis (Mirjam Holleman); Chapter 21: Different, not less: Communicating autism via the internet in Indonesia (Hersinta); Chapter 22: Making the irrelevant relevant: The case of the invisibles with disabilities in the Middle East (Najma Al Zidjaly); Part Five, Perspectives of Experience; Chapter 23: Human doing to human being: Western versus Indigenous views on differences in ability (Jillian Pearsall-Jones, Caris Jalla and George Hayden); Chapter 24: Strange beauty: Aesthetic possibilities for desiring disability into the future (Eliza Chandler and Esther Ignagni); Chapter 25: The Brazilian way: Media coverage of the London 2012 Paralympic Games (Tatiane Hilgemberg); Chapter 26: I could see the future: An ethnographic study of Deaf childrens transition from an oral school to a signing school (Pamela G Macias); Glossary; Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Disability studies; Interdisciplinary approach to knowledge; Interdisciplinary research; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / People with Disabilities; Electronic books